2015
DOI: 10.1002/ejlt.201500220
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated linoleic acid (CLA) influences muscle metabolism via stimulating mitochondrial biogenesis signaling in adult‐onset inactivity induced obese mice

Abstract: Recently, conjugated linoleic acid (CLA) has been reported to prevent body weight gain and fat accumulation in part by improving physical activity in mice. The current study was conducted to determine the role of CLA on skeletal muscle metabolism in nescient basic helix-loop-helix 2 knockout (N2KO) mice, an adult-onset inactivity induced obese model. Five-week-old female N2KO and wild type mice were fed either control or CLA containing diet (0.5%) for 10 wk. Voluntary activity was determined biweekly and marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 72 publications
5
5
0
1
Order By: Relevance
“…In the current study, CLA supplementation facilitated PGC-1α, PPARδ and PGC-1α-NRF-1-Tfam signaling cascades, implying that CLA may have potentiated mitochondrial biogenesis. This observation is consistent with the previous study where CLA isomers induced mitochondrial biogenesis via modulating the same signaling pathway [8,9].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In the current study, CLA supplementation facilitated PGC-1α, PPARδ and PGC-1α-NRF-1-Tfam signaling cascades, implying that CLA may have potentiated mitochondrial biogenesis. This observation is consistent with the previous study where CLA isomers induced mitochondrial biogenesis via modulating the same signaling pathway [8,9].…”
Section: Discussionsupporting
confidence: 94%
“…Earlier studies reported that 0.5% CLA supplemented mice increased voluntary movement (non-exercise physical activity) [7,8,19,20]. However, we did not observe an overall CLA effect on voluntary movement, consistent with a previous publication with exercise [6].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Park et al, () and Pariza et al, () noted that reductions in body fat in model animals appeared to be mainly due to lower body fat accretion induced by CLA. This effect was explained by the increased energy expenditure and physical activity of the CLA‐treated subjects (Kim, Kim, Good, & Park, ). Pariza et al, () also suggested that muscle mass may be preserved or enhanced as a consequence of CLA‐induced changes in the profile of cytokines affecting skeletal muscle catabolism and immune function.…”
Section: Discussionmentioning
confidence: 99%